The Effect of Plant Growth Promoting Bacteria on Transplants Growth and Lettuce Yield in Organic Production - Szczech Magdalena; Szafirowska Anna; Kowalczyk Waldemar; Szwejda-Grzybowska Justyna; Włodarek Agnieszka; Maciorowski Robert (Journal of Horticultural Research, 2016)
Application of beneficial bacterial strain B125 (Enterobacter sp.) and strain PZ9 (Bacillus sp.) in lettuce transplants production significantly enhanced seed germination and plant biomass. The best effect was obtained when the mixture of B125 and PZ9 was used. Combined application of these bacteria significantly increased transplants biomass, which was about 45% higher than that in the control. However, after planting these transplants in organic field, generally, there were no differences in yield and nutrient content in plants treated and not treated with the bacteria, except for nitrogen and vitamin C. The lettuce grown from transplants treated with bacterial mixture B125 + PZ9 contained significantly higher nitrogen than plants from other treatments. Opposite to nitrogen, bacterial applications decreased the amount of vitamin C. The growth and organic lettuce composition was affected by planting time. The yield was higher in spring, but the concentration of nutrients in these plants was lower than that in plants harvested in autumn. Climatic and light conditions in the late season were the reasons for increased dry matter content, minerals, phenolic compounds, and vitamin C, as well as high concentration of nitrates.